2020
DOI: 10.1016/j.jamda.2020.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Using Electronic Consultation in Long-Term Care Homes

Abstract: Patients in long-term care (LTC) homes face barriers to accessing specialist advice. Electronic consultation (eConsult) has the potential to improve access for these patients. We used a multi-method approach to evaluate adoption of the Champlain BASE eConsult service in LTC homes across Eastern Ontario, Canada. We conducted a cross-sectional study of all eConsults submitted by primary care providers (PCPs) working at LTC homes between January 1, 2018 and December 31, 2018. Service use data were collected and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(82 citation statements)
references
References 10 publications
2
76
0
2
Order By: Relevance
“…The integrated health network of Eastern Ontario has demonstrated the feasibility of using e-consultation for specialty care such as dermatology and infectious disease and identified perceived value with respect to timeliness, quality of care, and cost. 10 Similarly, investigators in the AMDA Telemedicine workgroup conducted a study of the perceived value of subspecialty telemedicine that showed that dermatology, geriatric psychiatry, and infectious disease were the specialties that PALTC practitioners would consult the most if available. 11 Similarly, many have called for reimbursement models to further expand reimbursement for telemonitoring and other telephonic-based care modalities.…”
Section: Regulatory Changes Due To Covid-19 Change the Landscapementioning
confidence: 99%
“…The integrated health network of Eastern Ontario has demonstrated the feasibility of using e-consultation for specialty care such as dermatology and infectious disease and identified perceived value with respect to timeliness, quality of care, and cost. 10 Similarly, investigators in the AMDA Telemedicine workgroup conducted a study of the perceived value of subspecialty telemedicine that showed that dermatology, geriatric psychiatry, and infectious disease were the specialties that PALTC practitioners would consult the most if available. 11 Similarly, many have called for reimbursement models to further expand reimbursement for telemonitoring and other telephonic-based care modalities.…”
Section: Regulatory Changes Due To Covid-19 Change the Landscapementioning
confidence: 99%
“…91% of PCPs rate the response as helpful and 60% of PCPs agree the case would be educational for their peers (Champlain BASE™ eConsult Service, 2017–2018). Further, previous work found that eConsult provided LTC PCPs with a new or additional course of action in 60% of cases ( Helmer-Smith et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…Given the limited access to specialist advice within LTC homes, challenges associated with external transfer, restrictions related to COVID-19 and infection control, and eConsult’s proven ability to facilitate high-quality, specific and helpful PCP-specialist communication about a residents’ care, eConsult is highly applicable to the LTC setting. Through eConsult, residents and their PCPs are able to obtain specialist advice to treat/manage the residents’ condition(s) and inform care planning, often without the need for a face-to-face specialist visit (70%) ( Helmer-Smith et al, 2020 ). In this way, eConsult is improving equitable access to specialist advice, supporting clinical decision-making, helping to address traditionally unmet needs, and improving residents’ quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations